Diversity of Bivalvia, Gastropoda and Holothuroidea in Intertidal Zone of North Javan Sea Coastal, Indonesia - V. Rohmayani; E. Tunjung Sari M.; Nurhidayatullah Romadhon; H. Ichda Wahyuni (Universitas Andalas, 2021)
This study aims to know diversity of Bivalvia, Gastropoda and Holothuroidea. Measures used in this study were Density Index (D), Diversity Index (H’), Evennes Index (E’) dan Important Value Index (INP). This study used transect sampling method by 1 × 1 meter quadrant. Target species of this study were member of Bivalvia, Gastropoda and Holothuroidea that inhabit in intertidal zone of north Javan Sea coastal. This intertidal zone was divided into 3 zone; zone I is 50 meter, zone II is 75 meter and zone III is 100 meter from coastal line to sea. Total sample of this species were 1064 individual, that divided into 7 species of Bivalvia, 10 species of Gastropoda and 2 spesies of Holothuridea. The highest Diversity Index was for Gastropoda in zone I (253 individual/m2). Diversity Index was in moderate category (1< H’ < 2) while the zone III was the highest. Evennes Index of all zones were relatively similar. The highest Important Value Index was species of Clypeomorus clypeomorus, that has value 53,06%.